Hubungan Antara Ph Plak Terhadap Terjadinya Early Childhood Caries (Ecc) pada Daerah Endemik Gizi Buruk - Pindobilowo; Febriana Setiawati; Riska Rina Darwita (Denta Journal Kedokteran Gigi, 2016)
Background: One of the prevention for Early Childhood Caries (ECC) is maintain daily food through limiting cariogenik food’s consumption, controlling eating frequency, improving oral and dental health. Dental caries would be prevented by controlling eating frequency, improving oral and dental health, so pH plaque can also be controlled. Purpose: Analyze the relationship between the pH plaque to ECC occurrence in an endemic area of malnutrition status. Materials and Methods: Cross section study on 287 children aged 6-48 months in an endemic area of malnutrition in the district Neglasari, Tangerang city in 2013, interviewing the mother, and intraoral examination in children, multistage cluster random sampling method. Result: ECC highest proportion found in plaque pH from 6.0 to 6.4 as much as 79.2% with a value of p = 0.000 (p<0.05) and is one of the better predictors of the occurrence of ECC. Conclusions: There isa significant relationship between pH plaque to ECC occurrence, this variableis accordant with the prevention of ECC because itis included inthe model predictors of ECC.